ANALISIS PERBEDAAN KINERJA KEUANGAN PADA KOPERASI MANDIRI DI KABUPATEN BANYUWANGI ATAS JASA KANTOR AKUNTAN PUBLIK - Yuhertiana, Indrawati; Sofyan, dan Donny Arsilo (Jurnal Strategi Akuntansi, 2009)
The purpose of this research is to examine the role of public accountant in its assistance in co-operation work. Therefore, it was examined the difference of co-operation financial performance in co-operation that haveÂ  accountant public assistance and co-operation that have not accountant public assistance. The role of public accountant to consultate co-operation in improving their skill in accounting is needed. Hopefully by the assistance of a public accountant, co-operation can improve their financial performance, so the entity could eficiently operationalized. Sample of this research are co-operation that located in Banyuwangi. Financial performance ratios, those areÂ  net prpft margin ration, current ratio and debt ratio used as variables in this research. The statistics tools to examine the hypotheses is T test. The research found that there are no differences in co-operation that use accountant public and none. There are three sectors that giveÂ  contribution in Indonesia economics, those are private sectors, co-operation and public sectors. Co-operation, that frequently called as âsoko guruâ Indonesia economics do not have a significant development. ThereÂ  are many evidence that make co-operation have a bad performance, many trouble in mismanagement, that make this institusion are not developed. Â  Keywords: Net Profit Margin, Current Ratio, Debt Ratio, Financial Performance, Co-Operation, Public Accountant